Recursive formulae for the multiplicative partition function - Jun Kyo Kim; Sang Guen Hahn (International Journal of Mathematics and Mathematical Sciences)
For a positive integer n, let f(n) be the number of essentially different ways of writing n as a product of factors greater than 1, where two factorizations of a positive integer are said to be essentially the same if they differ only in the order of the factors. This paper gives a recursive formula for the multiplicative partition function f(n).